Custodiol-N, the novel cardioplegic solution reduces ischemia/reperfusion injury after cardiopulmonary bypass - Veres, Gábor; Radovits, Tamás; Merkely, Béla; Karck, Matthias; Szabó, Gábor (Journal of cardiothoracic surgery, 2015)
On the basis of Custodiol preservation and cardioplegic solution a novel cardioplegic solution was developed to improve the postischemic cardiac and endothelial function. In this study, we investigated whether its reduced cytotoxicity and its ability to reduce reactive oxygen species generation during hypoxic condition have beneficial effects in a clinically relevant canine model of CPB.